1999
DOI: 10.1046/j.1365-2850.1999.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic communication strategies used by Hong Kong mental health nurses with their Chinese clients

Abstract: Therapeutic communication is central to mental health nursing and through this process nurse-client relationships can be enhanced. In Hong Kong, mental health nurses are educated in 'western' theories and strategies in using therapeutic communication and the field of communication is predominantly Eurocentric. However, the majority of people in Hong Kong are Chinese and little research has been conducted into how Hong Kong nurses communicate with their Chinese clients. This qualitative study focused on identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The nurses who were involving families more tended to be working in the out patient or community mental health care settings. Previous reported research with psychiatric nurses in Hong Kong indicated those working in the community tended to be more consistent in using supportive-expressive, analytic, and consultative approaches than did the nurses working in the acute psychiatric care setting (Arthur et al, 1999). Community mental health nurses also deliver care closer to the context of family than nurses in the acute care setting.…”
Section: Contextual Factors Related To No Changementioning
confidence: 93%
See 1 more Smart Citation
“…The nurses who were involving families more tended to be working in the out patient or community mental health care settings. Previous reported research with psychiatric nurses in Hong Kong indicated those working in the community tended to be more consistent in using supportive-expressive, analytic, and consultative approaches than did the nurses working in the acute psychiatric care setting (Arthur et al, 1999). Community mental health nurses also deliver care closer to the context of family than nurses in the acute care setting.…”
Section: Contextual Factors Related To No Changementioning
confidence: 93%
“…This may be because many of the educational models taught in the psychiatric nurse education curriculum are adapted from the West and are also individually focused. In addition, psychiatric treatment strategies tend to be didactic and directive, which contradict many of the postmodern ideas evolving in health care today (Arthur, Chan, Fung, Wong, & Yeung, 1999). There is also a predominance of the medical model in the health care system in Hong Kong that has a major influence on nursing.…”
mentioning
confidence: 99%
“…Hong Kong's mental health care system, since its inception has been influenced by British models of institutional care, and until recently little research has been conducted into the unique cultural needs of the majority of clients who are Chinese (Arthur et al 1999). As community focused care begins to take shape in Hong Kong (Health and Welfare Bureau 2000;Hong Kong Government 1991) and mental health workers begin to acknowledge the importance of a model of care which encompasses the needs of local people, in-depth studies are needed to provide an important foundation.…”
Section: Introductionmentioning
confidence: 99%
“…Cultural factors influence communication patterns. Chinese people are more submissive and passive in the presence of authority (Wu 1982), and Chinese patients expect a community nurse, as an authority figure, to give expert advice to solve their health problems (Arthur et al. 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Cultural factors influence communication patterns. Chinese people are more submissive and passive in the presence of authority (Wu 1982), and Chinese patients expect a community nurse, as an authority figure, to give expert advice to solve their health problems (Arthur et al 1999). However, existing satisfaction questionnaires developed in Western countries included items that required patients express their feelings towards the nurses (Gilleard & Reed 1998).…”
Section: Introductionmentioning
confidence: 99%